The Role Of Multimedia In The Process Physical Education Learning: Study Literature - Tri Prasetyo; Randi Kurniawan; Raffiandy Alsyifa Putra; April Yesaya Sipayung (Journal Sport Science Indonesia, 2024)
Education in the era of globalization means the integration of national education into world education. Students must be equipped with adequate competencies to be able to develop in the highly competitive digital era. There are several problems and challenges facing the world of education in the digital era, including the quality of education, professionalism of teaching staff, culture (acculturation), learning strategies, challenges for improving management, and challenges for advances in science and technology. The development of physical education needs to utilize multimedia to meet the needs of teachers and students in facing the era of industrial revolution 4.0. The use of multimedia in supporting the success of physical education learning needs to be developed from its various functions. The aim of this literature review is to identify and analyze research trends, data collection and search methods in the 2012-2022 time period. Articles are selected according to the topic, namely multimedia in physical education and published online by the Journal "Pedagogy of Physical Education and Sports". The results of the analysis show that the use of multimedia in physical education is not only limited to providing learning media, but can be used as an assessment instrument and study of sociological phenomena of interactions between teachers and students in achieving learning goals.